Facies model for a coarse-grained, tide-influenced delta: Gule Horn Formation (Early Jurassic), Jameson Land, Greenland - Eide, Christian Haug; Howel, John A.; Buckley, Simon John; Martinius, Allard W.; Oftedal, Bjørn Terje; Henstra, Gijs Allard (Sedimentology, 2016)
Tide-dominated deltas have an inherently complex distribution of heterogeneities on several different scales, and are less well-understood than their wave- and river-dominated counterparts. Depositional models of these environments are based on a small set of ancient examples, and are therefore immature. The Early Jurassic Gule Horn Formation is particularly well-exposed in extensive sea-cliffs from which a 32 km long, 250 m high virtual outcrop model has been acquired using helicopter-mounted lidar. This dataset, combined with a set of sedimentological logs, facilitate interpretation and measurement of depositional elements and tracing of stratigraphic surfaces over seismic-scale distances. The aim of this paper is to use this dataset to increase the understanding of depositional elements and lithologies in proximal, unconfined, tide dominated deltas from the delta plain to prodelta. Deposition occurred in a structurally controlled embayment, and immature sediments indicate proximity to the sediment source. The succession is tide-dominated but contains evidence for strong fluvial influence and minor wave-influence. Wave-influence is more pronounced in transgressive intervals. Nine architectural elements have been identified, and their internal architecture and stratigraphical distribution has been investigated. The distal parts comprise prodelta, delta front and unconfined tidal bar-deposits. The medial part is characterized by relatively narrow, amalgamated channel-fills with fluid mud-rich bases and sandier deposits upwards, interpreted as distributary channels filled by tidal bars deposited near the turbidity maximum. The proximal parts of the studied system are dominated by sandy distributary channel and heterolithic tidal-flat deposits. The sandbodies of the proximal tidal channels are several kilometres wide, and wider than exposures in all cases. Parasequence boundaries are easily defined in the prodelta to delta front environments, but are difficult to trace into the more proximal deposits. This article ...